Features of application of punishments without isolation of convict from society and determination of their purposes in the legislation of foreign countries: comparative legal analysis - Mayorova, Elena O. (Journal of the Belarusian State University. Law, 2020)
This article contains a comparative legal analysis of both fixing and applying penalties of the alternative penitentiary bloc in foreign countries, and determining their goals in the execution process. Attention is drawn to the refusal of the majority of foreign countries to legislate the goals of criminal punishment, including without isolating the convicted person from society, which seriously complicates the activities of the judicial and law enforcement agencies in the appointment and execution of sentences, and reduces the quality of justice. The author concludes that the consolidation in the criminal law of Russia, as well as a number of neighboring countries, of the institution of the goals of criminal punishment characterizes their legal system as developed, consistent with the main global trends and directions in the field of their purpose and execution, indicating the importance for the legislator of the final result which is to prevent the commission of new crimes.
Keywords: punishment without isolation of the convict from society; the purpose of criminal punishment; correction of the convict; re-education of the convict; prevention of new crimes; intimidation; retaliation; community service; fine; confiscation of property